Ajuda mútua nos CAPS: o papel dos serviços no empoderamento dos usuários - Figueiró, Rafael de Albuquerque (2009)
The research objective is explore practices to mutual help between CAPS users from the east and west regions of the city of Natal, RN, in Brazil. In the mental health field, we observe the care from substitutive services is based on technical knowledge where the person of the mental health professional is predominant. The Brazilian psychiatry reform invests in equipments and mental health care protocols, but it is necessary to invest more vigorously in new strategies and actors capable of obtaining resources to achieve this goal, such as the users. If one cornerstone of the psychiatric reform consists of changing the type of relationship established with the person with mental disorders, why this relationship, nowadays, is still dominated by technique and unevenness, where on one side we have a person who knows something and who needs take care of someone, and on other side we have another who knows nothing and thus needs to be cared for? Starting from this problematization of the traditional methods of health/mental health care, an attempt was made to investigate in what ways the mutual help practices between people with mental disorders can realize potential avenues not yet explored within the scope of psychiatric reform. The objective of this research was to map possible mutual help practices among the users, and the technical understanding of such practices. For that, we took part in the daily activities of the CAPS, mapping the experiences of mutual help among users. In addition, we accompanied the users in external activities (such as return home, trips, etc), and we had roundtables with the professionals. The research was guided by theoretical methodological references of the institutional analysis. The results pointed to a lack of behaviors of mutual help or support among users, something that can probably be explained by the service work dynamics, as well as the relationship between technicians and users, which has a tendency to create hurdles for meetings among users, as well as being non-conducive to theirempowerment